Study on Chinese College Teachers’ Professional Beliefs and Ways to Improve Their Professional Beliefs - Yang, Jie; Yao, Chunlin (Jurnal VARIDIKA, 2023)
Modern information technology has brought great benefits to education and challenged teachers’ professional beliefs. This study collects data about Chinese college teachers’ professional beliefs with the methods of questionnaire surveys and individual interviews. Based on 682 valid questionnaires, the study finds that Chinese college teachers’ professional beliefs are positive in general. Their research capabilities and their sense of research achievements are lower than their teaching abilities and their sense of teaching achievements. In addition, they expect to improve their information technology capabilities eagerly. Given research findings, this study proposes strategies to reconstruct the teachers’ professional beliefs, such as offering training and further education opportunities for college teachers, improving their research capabilities, intensifying the reform of colleges to establish a classified evaluation system, and providing information technology training for college teachers.